2020
DOI: 10.26434/chemrxiv.12228831
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Drug Repurposing Studies Targeting SARS-nCoV2: An Ensemble Docking Approach on Drug Target 3C-like Protease (3CLpro)

Abstract: <p>The COVID-19 pandemic has been responsible for several deaths worldwide. The causative agent behind this disease is the Severe Acute Respiratory Syndrome – novel Coronavirus 2 (SARS-nCoV2). SARS-nCoV2 belongs to the category of RNA viruses. The main protease, responsible for the cleavage of the viral polyprotein is considered as one of the hot targets for treating COVID-19. Earlier reports suggest the use of HIV anti-viral drugs for targeting the main protease of SARS-CoV, which caused SARS in the yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…79 These residues are mainly part of the S1 subsite (Asn142, Cys145 e Glu166) and S2 (His41 e Gln189), in addition, studies by Koulgi and collaborators suggest that the inhibitory effect is observed when interactions with these key residues occur at the active site of the enzyme. 80 Apart from remdesivir, application of darunavir against Covid-19 should be highlighted, especially since it has been studied as a possible treatment for SARS-CoV-2, and due to in vitro evidence that supports its ability to ght the disease. 81…”
Section: Virtual Screening and Molecular Docking Calculationmentioning
confidence: 99%
“…79 These residues are mainly part of the S1 subsite (Asn142, Cys145 e Glu166) and S2 (His41 e Gln189), in addition, studies by Koulgi and collaborators suggest that the inhibitory effect is observed when interactions with these key residues occur at the active site of the enzyme. 80 Apart from remdesivir, application of darunavir against Covid-19 should be highlighted, especially since it has been studied as a possible treatment for SARS-CoV-2, and due to in vitro evidence that supports its ability to ght the disease. 81…”
Section: Virtual Screening and Molecular Docking Calculationmentioning
confidence: 99%
“…Cefuroxime listed 8th and was concluded to attach with affinity energy of -9.2kcal/mol with an IC50 of 2.09mM [118]. Koulgi and co-workers [123] applying both a "direct docking" and an "ensemble docking" approach. The direct docking was a simple docking of promising medicines against the crystal structure of Mpro while the altogether coming included docking against variations in conformation of the active pocket of Mpro, which generally cause to perfect outcomes.…”
Section: In Silico Studies: the Potential Drug Candidates To Cure Covmentioning
confidence: 99%